2017
DOI: 10.1186/s12891-017-1551-z
|View full text |Cite
|
Sign up to set email alerts
|

A multimedia campaign to improve back beliefs in patients with non-specific low back pain: a process evaluation

Abstract: BackgroundLow back pain (LBP) is one of the most prevalent and costly disorders worldwide. To reduce its burden in the Netherlands, implementation of a multidisciplinary guideline for LBP was supported by a multifaceted eHealth campaign for patients with LBP. The current study aims 1) to evaluate whether the implementation strategy was performed as planned; 2) to assess the feasibility, barriers and facilitators of the patient based eHealth campaign; 3) to gain insight into the satisfaction and experiences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In the previous decades there has been an increase in the number of studies regarding primary prevention of MSD, across a wide range of scientific disciplines, including epidemiology (29), applied physiology (30), biomechanics (31), physical and organizational (macro) ergonomics (25,32), behavioral sciences (33), production engineering (34), organizational management (35), health and business economics (36), and implementation science (37). These disciplines vary largely in their contribution to work-related MSD prevention research, ranging from classic injury surveillance and etiological studies to detailed laboratory studies and animal models exploring injury mechanisms, and studies evaluating interventions and implementation.…”
Section: Van Der Beek Et Almentioning
confidence: 99%
“…In the previous decades there has been an increase in the number of studies regarding primary prevention of MSD, across a wide range of scientific disciplines, including epidemiology (29), applied physiology (30), biomechanics (31), physical and organizational (macro) ergonomics (25,32), behavioral sciences (33), production engineering (34), organizational management (35), health and business economics (36), and implementation science (37). These disciplines vary largely in their contribution to work-related MSD prevention research, ranging from classic injury surveillance and etiological studies to detailed laboratory studies and animal models exploring injury mechanisms, and studies evaluating interventions and implementation.…”
Section: Van Der Beek Et Almentioning
confidence: 99%
“…It is arguable that the participating patients were in good health states from the start and gaining much improvement on these functional outcomes was not realistic. Process evaluations among participating patients and professionals alongside the present study showed that compliance with the intervention was very low 20 21. Most patients did not comply to the full eHealth intervention: 31% of the participants had not used the campaign materials at all, and 42.9% had only used it once, and professionals almost never discussed the intervention with their patients.…”
Section: Discussionmentioning
confidence: 66%
“…The literature does not provide explanations for this fact. One explanation could lie, again, in the low compliance rate of patients in this study 20. On the other hand, the use of alternative care could be seen as self-management, because patients decide what they want, when they want it, and how much they are willing to pay for it.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations